PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN, DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021–2024 - Hania Tri Utami; Hestin Sri Widiawati; Erna Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of cash turnover, receivable turnover, inventory turnover, and leverage on profitability in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. This study uses a quantitative approach with purposive sampling technique, resulting in 18 companies as samples with 72 units of analysis. Secondary data were obtained from annual financial reports through the official IDX website. Analysis techniques include classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), t-test, and F-test using IBM SPSS Statistics 25. The results show that partially, cash turnover and leverage have a significant effect on profitability, while receivable turnover and inventory turnover do not have a significant effect. Simultaneously, all independent variables have a significant effect on profitability with a significance value of 0.014 < 0.05. The Adjusted R Square value of 14.0% indicates the ability of the independent variables to explain the variation in profitability.